2019
DOI: 10.1016/j.jcsr.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined bending and shear behaviour of slotted perforated steel channels: Numerical studies

Abstract: Cold-formed steel studs and purlins with staggered slotted perforations in webs are used in building structures to produce a better thermal performance of the profiles and for the energy efficiency of structures. On the other hand, the slotted webs result in an unfavourable effect in terms of the structural performance of the element, prominently their shear, bending and combined bending and shear strengths. Relatively little research has been reported on this subject despite its importance. Many research stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…19 shows the staggered slotted perforated cold-formed steel channel. The structural performance of these channels, when it is used as a beam, was investigated by Degtyreva et al [25] , [26] , [27] and found that the reduction of the maximum reduction bending capacity is only 23% and 11% for distortional and local buckling failure. Moreover, Gatheeshgar et al [73] introduced these staggered slotted perforations to optimised CFS beams for modular building applications.…”
Section: Development Of Affordable Modular Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…19 shows the staggered slotted perforated cold-formed steel channel. The structural performance of these channels, when it is used as a beam, was investigated by Degtyreva et al [25] , [26] , [27] and found that the reduction of the maximum reduction bending capacity is only 23% and 11% for distortional and local buckling failure. Moreover, Gatheeshgar et al [73] introduced these staggered slotted perforations to optimised CFS beams for modular building applications.…”
Section: Development Of Affordable Modular Unitmentioning
confidence: 99%
“…The objective of these optimisation studies was to maximise the structural capacity of CFS structural members for a given amount of material. Moreover, modifying CFS beams through providing staggered slotted perforations is efficient to enhance the thermal performance while the effect of staggered slotted perforations on flexural capacity is minimal [25] , [26] , [27] . These findings can be incorporated into steel-framed modular buildings to ensure more economical and efficient design solutions.…”
Section: Introductionmentioning
confidence: 99%
“…They are focused on meeting the physical, aesthetic and other needs of a person. These are retrofuturism and futurism [8], bio-tech [9], eco-architecture [10][11].…”
Section: Search and Analysis Of Architectural Styles And Constructionmentioning
confidence: 99%
“…However, the slotted perforated regions were provided with 1.5 mm × 5 mm mesh refinement, where 1.5 mm of maximum element size in the vertical direction and 5 mm maximum element size in the longitudinal direction in the perforated region. Similar mesh refinements were also used to study the shear [7] and combined bending and shear [8] behaviour of slotted perforated CFS channels. Fig.…”
Section: Mesh Controlmentioning
confidence: 99%
“…The shear behaviour of slotted perforated CFS channels has been investigated through structural tests [6] and numerical modelling [7] and it was found that the ultimate shear capacity was reduced up to 70% due to the presence of slotted perforations in the web. Degtyreva et al [8] investigated the combined bending and shear behaviour of slotted perforated CFS channels through the numerical analysis and presented design proposals to predict the combined bending and shear capacity. Numerous experimental and numerical research studies have been performed to study the flexural behaviour of Csections, Z-sections, and hollow flange sections with solid webs [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%